2009
DOI: 10.3174/ajnr.a1615
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Shows Different Topographic Involvement of the Thalamus in Progressive Supranuclear Palsy and Corticobasal Degeneration

Abstract: BACKGROUND AND PURPOSE:In progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD), postmortem studies show different topographic involvement of the thalamus, basal ganglia, and their cortical connections. Diffusion tensor imaging (DTI) is an MR imaging technique sensitive to gray and white matter microstructure integrity. This study was performed to determine whether DTI may demonstrate microstructural differences between PSP and CBD, particularly within the thalamus and its cortical connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 43 publications
9
67
0
Order By: Relevance
“…Three studies 17,28,40 compared participants with corticobasal syndrome and controls (table e-1). A VBA study 40 showed primarily cortical reduction of FA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies 17,28,40 compared participants with corticobasal syndrome and controls (table e-1). A VBA study 40 showed primarily cortical reduction of FA.…”
Section: Resultsmentioning
confidence: 99%
“…Progressive supranuclear palsy. Frontal white matter FA was investigated in 2 ROI studies 6,28 ; both detected reductions in patients vs controls (table e-1). One VBA study 30 also detected significant frontal FA reductions but another TBSS study 29 did not.…”
Section: Resultsmentioning
confidence: 99%
“…5 The presence of AOS is associated with corticobasal degeneration pathology 5 and previous studies of corticobasal syndrome have similarly reported diffusivity changes in the supplemental motor area and frontoparietal fibers, which likely coincide with the superior SLF. 38,39 Detailed speech and language assessments were not available for the subjects in this study, however, and therefore the contribution of these motor problems is presently unclear.…”
Section: Gray Matter Voxel-level Analysesmentioning
confidence: 99%
“…Previous studies of PD and atypical parkinsonisms demonstrated thalamic abnormalities by using region-of-interest or voxelwise approaches. [9][10][11][12][13] MR imaging-based analysis of the shape of the subcortical structures provides useful pieces of information about the location and pattern of structural abnormalities associated with these pathologic conditions. Using such an approach, several studies reported regional thalamic damage in patients with schizophrenia, obsessive-compulsive disorders, Alzheimer disease, and Tourette syndrome.…”
mentioning
confidence: 99%